Standardisation Of Macro And Micro Propagation Techniques In Bougainvillea - Aishabi KA (Department Of Pomology And Floriculture, College Of Horticulture, 1985)
The present investigations were carried out at the College of Horticulture, Kerala Agricultural University, during 1983-84 to standardise the asexual propagation in bougainvillea through conventional as well as micropropagation techniques. For macrcpropagation studies, cuttings from nine varieties were treated with IBA and NAA each at 100,300, 750 and 1000C ppm concentrations. The results revealed that all the treatments, particularly IBA were significantly superior to the control. Soaking the basal ends of the cuttings in IBA 500 ppm solution for a period of six hours, gave maximum percentage of rooting both in rainy and summer seasons. The rooting response of different varieties varied considerably. Maximum percentage of rooting was obtained in the variety ‘Jayalakshmy’ and minimum in ‘Cherry Blossom’ during both the seasons. Organic carbon and total nitrogen content showed a significant negative correlation with percentage of rooting, A positive correlation was however observed between C/N ratio and rooting percentage. Rooting was more when the rainfall was maximum and variation in mean temperature was less. Root number, root length and root weight were significantly increased in all the auxin treated cuttings than in the control. Number of roots, length and fresh weight of roots/cutting were more during rainy season, than in summer. Fresh weight of the shoot/cutting and shoot/root ratio were more during summer than in rainy season. Micropropagation studies carried out using the explants from ‘shy’ rooting varieties of bougainvillea indicated that, of the different explant sources tried, shoot apices and immature axillary stem segments were the most potent sources for callus formation. All the three auxins tried namely, IAA, NAA and 2,4-D were capable of initiating callus, but 2,4-D delayed the period of initiation, .'MS medium supplemented with NAA and BA was found to be most suitable for callus formation, and maximum number of cultures cullused in the presence of NAA 1.0 mg/1 + BA 0.5 mg/1, KIN was found to be less effective than BA. Maximum number of cultures callused, in the case of explants collected from the variety ‘Mahara’, compared to that from ‘Cherry Blossom’ and ‘Spring Festiva’. Attempts to induce proliferation of axillary buds showed that, MS medium containing BA 2.0 mg/l + IAA 1.0 mg/l was optimum. Higher concentrations of BA (9.0 mg/l and above), though Induced more number of shoots, they were abnormal and unhealthy. Addition of adenine sulphate 50 mg/l produced a synergistic effect on shoot production. Fresh shoot apices and precallused shoots rooted readily on full and half strength MS medium supplemented with different auxins like IAA, NAA and IB A. Percentage of rooting was maximum on half strength MS medium in the presence of IBA 1.6 mg/l. The time required for root initiation was reduced on half strength MS medium and further when precallused shoots were used. Field transplantation of the rooted plantlets was not successful and further studies In this espect is necessary.